The Role of National Human Rights Institutions, the Unicef, and Non-governmental Organisations in the Implementation of the United Nations Convention on the Rights of the Child - Benyusz , Márta (International Children's Rights, 2024)
The United Nations Convention on the Rights of the Child (CRC) is the most widely ratified human rights treaty in the world. The CRC declares the rights of children and defines a minimum level of protection applicable to all state parties for each child. Children’s rights are human rights, and as such, their addressees are first and foremost the states. In other words, the states are those primarily responsible for and entitled to the implementation of children’s rights as per the CRC. Nevertheless, there are other organs that played important roles in the process of drafting and adopting the CRC and its Optional Protocols, and which remain adding special expertise and giving echo to the voices of stakeholders (e.g. parents, churches, and children) amid the continuous implementation of the CRC. The importance of their roles is also articulated in Art. 45 of the CRC. Accordingly, this chapter delves into the United Nations Children’s Fund (UNICEF; as an intergovernmental organisation), non-governmental organisations, and national human rights institutions, along with the respective roles they played in the drafting and adoption of the CRC and continue to play in its implementation and monitoring.Keywords: United Nations Convention on the Rights of the Child, rights of the child, non-governmental organizations, UNICEF, national human rights institutions, adoption, implementation, monitoring